The Image of the European Union and the United Kingdom in the Brexit Media Discourse: A Study of the Lexicon Used by the Spanish Press - Ramos Ruiz, Álvaro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The media have an important persuasive power over the audience. One of the most relevant media phenomena in recent years was Brexit. The objective of this study is to find out the editorial position of the Spanish press in relation to the actors of Brexit (European Union and United Kingdom). To do this, a lexical analysis based on the Frame Semantics was carried out. The results of the investigation shown that Spanish newspapers maintained a pro-European stance throughout the entire Brexit process.